Evaluation of the possibility of using an antenna switch with a wideband matching device - Zhanat Manbetova; Assel Yerzhan; Zharkyn Altynov; Zukhra Rakhimzhanova; Gulzada Mussapirova; Pavel Boykachev; Assanali Iskakov; Maria Poleshchuk (Bulletin of Electrical Engineering and Informatics, 2026)
This paper investigates the feasibility of integrating a broadband matching device (BMD) with a high-frequency switch into the antenna system of the MIC RL-400M radio relay station, part of the "ROSA" radar complex. The aim is to compensate for antenna impedance changes caused by adverse weather conditions such as snowfall, icing, and wet snow, which reduce power transmission efficiency. Various types of high-frequency switches, including relays, PIN diodes, and transistors, were analyzed. A transistor-based switch (HMC349AMS8G) was selected due to its low insertion loss, high reliability, and wide operating frequency range. The BMD structure was synthesized to minimize impedance variation, and its performance was evaluated through simulation in AWR Microwave Office and experimental measurements in the 394–450 MHz range. Results showed an average power loss reduction of 0.7 dB and a 6.9% increase in radio link range compared to operation without a switch. The proposed solution enhances the stability and efficiency of radar and radio relay systems, ensuring reliable operation in challenging environmental conditions.